Particulate matter characteristics, dynamics, and sources in an underground mine. Issue 1 (2nd January 2018) - Saarikoski, S.; Teinilä, K.; Timonen, H.; Aurela, M.; Laaksovirta, T.; Reyes, F.; Vásques, Y.; Oyola, P.; Artaxo, P.; Pennanen, A. S.; Junttila, S.; Linnainmaa, M.; et al.
ABSTRACT: Particulate matter (PM) from mining operations, engines, and ore processing may have adverse effects on health and well-being of workers and population living nearby. In this study, the characteristics of PM in an underground chrome mine were investigated in Kemi, Northern Finland. The concentrations and chemical composition of PM in size ranges from 2.5 nm to 10 µm were explored in order to identify sources, formation mechanisms, and post-emission processes of particles in the mine air. This was done by using several online instruments with high time-resolution and offline particulate sampling followed by elemental and ionic analyses. A majority of sub-micrometer particles (<1 µm in diameter, PM1 ) originated from diesel engine emissions that were responsible for a rather stable composition of PM1 in the mine air. Another sub-micrometer particle type originated from the combustion products of explosives ( e.g., nitrate and ammonium). On average, PM1 in the mine was composed of 62%, 30%, and 8% of organic matter, black carbon, and major inorganic species, respectively. Regarding the analyzed elements ( e.g., Al, Si, Fe, Ca), many of them peaked at >1 µm indicating mineral dust origin. The average particle number concentration in the mine was (2.3 ± 1.4)*10 4 #/cm 3 . The maximum of particle number size distribution was between 30 and 200 nm for most of the time but there was frequently a distinct mode <30 nm. The potential origin of nano-size particles remained as challenge for future studies. Copyright © 2018 The Authors. Published with license by Taylor & Francis